Acute Physical Therapy Competency for Identifying Appropriate Patients for a Physical Therapist Assistant's Caseload. Issue 3 (July 2020) - Powell, Debra; Roberts, Pamela; Truong, Lyna
Abstract : Background: At an academic medical center, physical therapist assistants (PTAs) were observed spending increased time reviewing charts and collaborating with the physical therapists (PTs) about inappropriate patient caseloads. Objective: To develop staff competency through a standardized process for the identification of appropriate patients for a PTA caseload utilizing the APTA's PTA Direction Algorithm and improve PT/PTA relationships in the acute care setting. Design: Mixed-methods prospective study. Methods: Study consisted of acute care PT staff in an academic medical center using the PTA Direction Algorithm with data collected, pre- and posttraining of the PT staff in the algorithm, and the Mann-Whitney U test was used to determine statistical differences. Focus groups with the PTAs were conducted pre- and posttraining of the PT staff. Results: Data were collected from the 2 participating PTA staff for a period of 294 total worked hours both for the pre- and posttraining periods. For the pretraining period, data were collected between April 1, 2018, and April 28, 2018, for 28 days with 302 patient care encounters. The posttraining period occurred between July 1, 2018, and August 11, 2018, for 42 days with 307 patient care encounters. The PTAs' daily average pretraining of 10.79 patient encounters, 40.71 minutes for chart reviews, and 12.89 minutes for PT/PTA collaboration decreased posttraining, to a daily average of 7.31 patient encounters, 6.43 minutes for chart reviews, and 6.76 minutes for PT/PTA collaboration. PTAs spent significantly less time in daily average reviewing of charts posttraining (mean = 6.43, SD 10.98, compared with the pretraining (mean = 40.71, SD 38.96, U = 186.500, P < .001). Collaboration times also significantly decreased posttraining (mean = 6.76, SD 11.14), compared with pretraining (mean = 12.89, SD 11.54, U = 371.00, P = .007); however, the average number of daily encounters unfavorably decreased in the posttraining (mean = 7.31, SD 5.13), compared with the pretraining period (mean = 10.79, SD 5.06, U = 398.5, P = .022). Limitations: Small number of participants in one academic medical center. Conclusions: The PTA Direction Algorithm tool used in establishing staff competency provided the mechanism for developing a standardized process, significantly improving chart review time, and PT/PTA relationships in the acute care setting.